Bisimulations in the Join-Calculus - Fournet, Cédric; Laneve, Cosimo (Programming Concepts and Methods, IFIP TC2/WG2.2,2.3 International Conference on Programming Concepts and Methods (PROCOMET '98), 2000)
We develop a theory of bisimulations in the join-calculus. We introduce a refined operational model that makes interactions with the environment explicit, and discuss the impact of the lexical scope discipline of the join-calculus on its extensional semantics. We propose several formulations of bisimulation and establish that all formulations yield the same equivalence. We prove that this equivalence is finer than barbed congruence, but that both relations coincide in the presence of name matching.